2004
DOI: 10.1149/1.1773731
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Kinetic Study of Olivine Li[sub x]MPO[sub 4] (M=Fe, Mn)

Abstract: A huge kinetic difference in olivine Li x MPO 4 (M ϭ Fe,Mn) is demonstrated in a quantitative manner. Galvanostatic discharge profiles and the current relaxation to the stepwise anodic overvoltage ͑chronoamperometry͒ are comparatively measured for the Li x FePO 4 and Li x MnPO 4 under identical extrinsic conditions, which are carefully controlled and confirmed using Rietveld refinement for the X-ray diffraction profiles, direct texture observation by scanning electron microscope, Brunauer-Emmett-Teller surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
265
1
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 390 publications
(277 citation statements)
references
References 41 publications
7
265
1
4
Order By: Relevance
“…In order to allow the Mn 2+/3+ redox reaction in a LiMnPO 4 cathode, the material needs to be both ionically and electronically conductive for Li + diffusion and electron transport, respectively. However, pure LiMnPO 4 material suffers from poor intrinsic electronic conductivity [10,11]. To improve the electrochemical kinetics, several groups, including previous work by us, reported the enhanced electrochemical properties, combining both, reduced particle size of LiMnPO 4 and carbon coating [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In order to allow the Mn 2+/3+ redox reaction in a LiMnPO 4 cathode, the material needs to be both ionically and electronically conductive for Li + diffusion and electron transport, respectively. However, pure LiMnPO 4 material suffers from poor intrinsic electronic conductivity [10,11]. To improve the electrochemical kinetics, several groups, including previous work by us, reported the enhanced electrochemical properties, combining both, reduced particle size of LiMnPO 4 and carbon coating [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Despite its nearly ideal potential of 4.1 V vs. Li/Li + , lithium manganese phosphate has been found to be an inferior cathode material compared to LiFePO 4 . 2,3 The much slower kinetics during Li extraction and insertion are directly related to fundamental differences, including lower electronic and ionic conductivities in LiMnPO 4 , the Jahn-Teller effect in Mn 3+ , larger interface strain due to the larger volume change between LiMnPO 4 and MnPO 4 , and the metastable nature of the delithiated phase.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 It was reported that the poor rate capability of LiMnPO 4 is ascribable to a large kinetic barrier at the mismatched interface of MnPO 4 / LiMnPO 4 during Li insertion/extraction processes and that down sizing the olivine particle to nanometer level would be effective to lower the kinetic barrier. 6 Since LiMnPO 4 is expected to have higher energy density than LiFePO 4 due to its higher redox potential of 4.1 V vs. Li/Li + (3.5 V vs. Li/Li + for LiFePO 4 ), various methods to synthesize nanosized LiMn-PO 4 particles have been developed in recent years for achieving reasonable capacity and rate. However, there is still a problem of poor electronic conductivity in the electrode because strong agglomeration of nanosized particles prevents homogeneous mixing with a conductive additive such as carbon black.…”
mentioning
confidence: 99%